2011
DOI: 10.1016/j.mce.2011.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Direct actions of ACTH on ovarian function of pseudopregnant rabbits

Abstract: 24 25The present study sought to assess whether the receptors for adrenocorticotropic hormone (ACTH), MC2R, and 26 for glucocorticoid (GR) are expressed in corpora lutea (CL) of pseudopregnant rabbits and whether ACTH and 27 cortisol exert any direct action on luteal function. By immunohistochemistry, positive reaction for MC2R and 28 GR was detectable within luteal cells of CL. The MC2R mRNA levels were five-fold less abundant in day 9 than 29 in day 4 CL (P<0.01). At both stages, ACTH agonist (ACTH 1-24) inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
(8 reference statements)
0
12
1
Order By: Relevance
“…The alteration of LH levels may influence progesterone secretion in CL. Furthermore, studies suggested that ACTH or cortisol could directly regulate formation and function of CL (40). However, the mechanism has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…The alteration of LH levels may influence progesterone secretion in CL. Furthermore, studies suggested that ACTH or cortisol could directly regulate formation and function of CL (40). However, the mechanism has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…; Guelfi et al . ), and ACVR1C (or ALK7 ), which is expressed in the corpus luteum and influences its metabolism (Galvao et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that CRH, glucocorticoids, and ACTH affect ovarian function at the hypothalamus and the pituitary gland levels to decrease the synthesis and release of gonadotropin-releasing hormone, luteinizing hormone (LH), and follicle-stimulating hormone (FSH), whereas others suggest that they act on the ovary to modulate steroidogenesis and/or oogenesis directly [18][19][20]. However, evidence regarding the direct effect of the HPA products on the oocyte is limited and conflicting.…”
Section: Introductionmentioning
confidence: 99%